MANAJEMEN KEPEMIMPINAN BERBASIS MUTU UNTUK MENINGKATKAN DAYA SAING PERGURUAN TINGGI - Sapendi Sapendi (AT-TURATS, 2016)
Leadership base qualify is a leadership that be able to apply qualify management well.one of flourish base qualify is Integrated Qualify Management (IQM)applying IQM needs the character change of relation between the one who managing (leader) and the one who doing work (lecturer, worker, laboratory assistant, technician, etc.). Command from the leader changed by the worker into initiative. Leader task not only give a command but also supporting and facilitating work qualify improvement of the members and the workers. To make leadership on a university can apply IQM successfully, then the university has to do systematic process. These are the concepts apply Determination-Implementation-Evaluation-Control-Enhancement (DIECE), that consist steps of plan, plan of implementation, implementation of evaluation, control and enhancement that corrective to the results.